SEPAKBOLA, KOMPETISI, DAN ANAK USIA DINI - Nawan Primasoni (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2016)
Once the child is expected to participate in this competition have higher motivation in playing and practicing during the competition, knowledge of the rules of the game, a lot of experience because of the frequency of matches, and a happy atmosphere, will eventually be able to improve their skills in playing football, especially in preparing for national championship .Maximum achievement that can be obtained with an ideal competition means a lot of competition is not done in a very short period of time from the preliminary round to the finals. A competition by changing the rules that are pertadingan enjoy a much needed children. Not only that but extrinsic motivation needed to keep children happy and not bored of the game of football. Keywords: football, competition, early childhood